THE EFFECT OF TALENT MANAGEMENT ON EMPLOYEE PERFORMANCE WITH CORPORATE CULTURE AS A MEDIATING VARIABLE - Ilham Ananto Yuwono; Arif Imam Suroso; Aida Vitayala Hubeis (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Talent management is a dynamic and comprehensive process for developing the highest potential employees in an organization through direct and integrated development. To increase revenue and capabilities according to the company's portfolio in the telecommunications sector, especially in digital services, the company initiated a talent management program in the form of an internal corporate start-up program. The internal corporate start-up program is an initiative program that aims to capture and accelerate digital business innovation from employees. However, the evaluation process is still focused on the produced products' business aspects, not on the human resources aspect. Therefore, it is necessary to evaluate the relationship between talent management programs and the improvement of company human resources (especially aspects of corporate culture and employee performance). Corporate culture is an important factor because the internal corporate start-up program is one way to encourage a culture of innovation in the corporate environment. The samples used were saturated samples, in which the population was all employees who were members of the internal corporate start-up program, 55 employees located in Jakarta. The data processing and analysis method used was structural equation modeling-partial least square (SEM-PLS). SEM-PLS analysis results showed that corporate culture directly affected employee performance and acted as a mediating variable between talent management and employee performance. Keywords: corporate culture, employee performance, human resources, SEM PLS, talent management